Growth and mortality of black bass, Micropterus salmoides (Pisces, Centrachidae; Lacapède, 1802) in a reservoir in southern Brazil - Schulz,U. H. (2005)
The black bass, Micropterus salmoides, was introduced to Brazil from North America in 1922. Since then the species has been reared in aquaculture facilities intended to stock reservoirs as additions to native stocks available for angling. At present no scientific information on the biology of black bass in Brazilian waters is available. Since black bass dispersion may cause severe impacts on native Brazilian fish fauna, information on the basic biological parameters of this species is necessary. The objective of the present study is to provide information on the growth, age structure, and mortality of the species in a small reservoir in southern Brazil, where the species reproduces regularly. Based on scale readings, the von Bertalanffy growth curve was calculated and compared to the length-frequency distribution of the population. Both methods showed similar results. Maximum length was about 44 cm. The mean length at the end of the first year was 23.1 cm (s.d. = 13.88); at that of the second, 37.3 cm (s.d. = 12.52); and 41.4 cm (s.d. = 9.92) at the third. Oldest fish were three years old. The growth performance index ø' was 3.28 cm year-1. Mortality increased from 0.16 year-1 between the first and the second cohort, to 0.8 year-1 between the second and third. The results show that black bass in Brazil grows faster than in its area of origin, but longevity is shorter and body shape, stouter. The cause of high mortality at a relatively early age may be connected with the loss of genetic diversity due to inbreeding of the Brazilian stocks, which originated from few introduced individuals a long time ago. The fact that black bass reproduces in reservoirs and grows rapidly may be considered a threat to conserving fish diversity in Brazilian ecosystems.